(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Many tocolytic agents are used to suppress preterm uterine contractions. These include: beta-agonists, calcium channel blockers, prostaglandin synthetase inhibitors, nitric oxide donars, oxytocin receptor antagonists. Among these the calcium channel blockers specifically nifedipine is constantly gaining importance due to its more effectiveness and lesser side effects as compared to the other drugs. In high risk pregnancies, Progesterones had also shown efficacy in reducing the incidence of recurrent preterm delivery . In this study the effectiveness of nifedipine with progesterone depot and nifedipine alone in the tocolysis of preterm labour was compared. Objectives: To determine the efficacy of nifedipine alone (group-A) and nifedipine with progesterone depot (group-B) for tocolysis of preterm labour. Study design: Randomized controlled trial Setting: Obstetrics and Gynaecology unit-III, Sir Ganga Ram Hospital, Lahore. Duration of study with dates: This study was conducted over period of six months from June 2015 to December 2015. Subjects and Methods: The study was conducted on 92 patients; i-e: 46 in each group at gestational age of 28-36weeks. Results: Age range in the study was from 18 to 35 years with mean age of 20.04 ± 5.12yaers. Majority of the patients 40 (43.48%) were between 18 to 25 years of age. The gestational age was from 28 to 36 weeks with mean age of 33.56 ± 2.23 weeks. Majority of the patients 51 (55.43%0were between > 32 to 36 weeks of gestation. Mean parity in group-A was 2.34±1.51 while in group-B was 2.46±1.39.There was cessation of uterine contractions till 48 hours in 22 (47.83%) and no cessation in 24 (52.17%) patients in group-A, nifedipine only ; while in group-B ,nifedipine with progesterone depot, it was seen in 33 (71.74%) and 13 (28.26%) patients respectively. So, efficacy was 47.83% in group-A and 71.74% in group-B with pvalue of 0.019. Conclusion: Through this study it was concluded that nifedipine with progesterone depot was more effective in cessation of preterm uterine contractions as compared to oral nifedipine alone. So, it is recommended that nifedipine with progesterone depot should be used as a first line agent to inhibit the uterine contractions in preterm labour. Thus some benefit can be achieved by prolongation of preganacy , by accelerating fetal lung maturity through administration of corticosteroids. And this would help fetomaternal outcome and reduce the complications related to prematurity .